SUSTAINABLE DEVELOPMENT AS THE CONCEPT OF SOCIAL PROGRESS - Ключко, В. Г. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The reasons and preconditions, which have promoted the development of the concept of sustainable development are analyzed, the process and the main stages of its strategy formation are examined in the paper. The characteristics of the three key components of sustainable development is given, the approaches to the implementation of such development are represented. The main achievements of sustainable development realization and the factors, which restrain its realization under current conditions, are defined. The actions needed, to the further development and the achievement of the sustainable development goals, are outlined.